OPERATION CHARACTERISTICS OF ELECTRIC TRAINS ER1, ER2 BEYOND DESIGNED SERVICE LIFE - Gorobets, V. L.; Bondarev, O. M.; Skoblenko, V. M. (Science and Transport Progress, 2014)
Purpose. The aim is to develop the scientific substantiation technical regulation of measures and conditions in electric trains, series ER1, ER2 beyond the extended period of operation life (over 50 years). Methodology. To achieve this goal the scientific publications analysis on the survivability of the basic elements of supporting constructions that are loaded with dynamic alternating loads was carried out. The results analysis of vibration bench tests of bogie frames of electric trains ER1, ER2, which were obtained by using the developed technique for such tests with authors, was carried out too. Technical solutions with appropriate measures under which it is possible to extend the operation life of bearing structures of electric trains ER1 and ER2 were developed over 50 years. Findings. Results were obtained on the complex basis of conducted experimental and theoretical research. They have promoted to the working out the methodology for assessing the period of crack development in the tensest points of main bearing structures of bogie frames and bodies of electric trains ER1, ER2 with achieving their dangerous sizes. This allowed developing a technical regulation measures to ensure the safe operation of the main bearing structures of bogie frames and bodies of electric trains ER1, ER2 beyond 50 years. Originality. To ensure the safe trains operation, series ER1, ER2 the method estimation of crack development term in the tensest points of bearing structures of bogie frames and bodies with achieving their dangerous sizes was worked out. Practical value. The technical regulation of measures ensuring the safe operation of the main bearing structures of bogie frames and bodies of electric trains ER1, ER2 beyond 50 years was developed.